Improving collaboration between primary care and mental health services - Kates, Nick; Arroll, Bruce; Currie, Elizabeth; Hanlon, Charlotte; Klasen, Henrikje; Meadows, Graham; Rukundo, Godfrey Zari; Sunderji, Nadia; Ruud, Torleif; Williams, Mark (The World Journal of Biological Psychiatry, 2018)
In almost any country – whether high, middle or low income - primary care providers play major roles in delivering mental health care. Indeed, the World Health Organization has recognized that in many low and middle-income countries, meeting the mental health needs of the population can only be achieved through greater integration of mental health services within primary care settings. Other guidelines and planning documents have reached similar conclusions and made suggestions as to how to achieve this. This position paper builds upon this work and synthesizes their ideas and recommendations into a framework for enhancing mental health care delivered within primary care settings. This framework is based upon principles that can be adapted to any context, rather than specific models. The paper identifies the key elements of successful collaboration and presents a three-step approach to improving collaboration. The first is the mental health services that any primary care provider can deliver, with or without the presence of psychiatrists or other mental health professionals. The second is practical ways in which effective collaboration can enhance and expand this care. This includes both the integration of mental health services within primary care and changes that any mental health service can make to better support local primary care providers. The third step looks at wider system changes required to support these new roles and activities, and how better collaboration can create new opportunities to respond to the challenges that all mental health systems are facing.
Keywords: Primary Care; Mental health services